Design of fractal minkowski diversity antenna for LTE and WIFI application - Ali, Munasar Abdirahman (2015)
The 4th Generation (4G) in which world has recently entered and many of the bigger operators and vendors have started deploying 4G networks in different countries. 4G includes higher releases of following two standards: Wireless Interoperability Microwave Access (WiMAX) and Long Term Evolution (LTE). In this project, the Minkowski fractal Array Diversity antenna is introduced. Fractal geometry allows us to design a miniature antenna and integrate multiple telecommunication services into single device. One of the most relevant trends for wireless devices is miniaturization. The purpose of this project is to design microstrip patch antenna and execute the first iteration Minkowski fractal Array Diversity antenna in order to achieve an antenna with multi-band frequency of 1.8 GHz and 2.4 GHz for LTE system and WIFI. Design process involves a mathematical analysis, simulation and fabrication process. Fractal antenna properties were observed from the measurement of return loss, standing wave ratio (SWR), bandwidth and radiation pattern.